The HIPC debt relief initiative: Uganda's social sector reforms and outcomes - Justine Nannyonjo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Uganda is the first country to benefit from the 1996 Heavily Indebted Poor Countries (HIPC) Initiative, which offers a number of low-income countries an opportunity to negotiate a reduction of their external debt, and is utilizing the savings from the relief to implement social sector reforms, via its poverty eradication action plan (PEAP). This paper assesses the performance of the social sector programmes being implemented. It indicates that even though some progress has been achieved in improving Uganda's social indicators, there are a number of constraints to the reform process: inadequate capacity particularly at the district and community levels; insufficient inputs including teachers and health personnel; and weak accountability of resources. However, implementation of programmes to solve these problems requires additional resources to those that are currently projected from domestic and donor sources, and it is estimated that there is likely to be a resource gap in the country's social development expenditure. An implication is that Uganda will require further financial support in order to be able to significantly improve its social indicators.
Keywords: O11; O19; F34; F35; 330; HIPC debt relief; social sector reforms; Uganda; Auslandsverschuldung; Schuldenerlass; Sozialpolitik; Uganda